CASE Weight Test: A hands on approach to comparing and selecting CASE tools at Twentieth Century Services - Eaton, Roger G.; Hayes, Karl W. (My University, 2016)
R.G. Eaton and Karl W. Hayes are spearheading the implementation oflnformation Engineering (IE) at Twentieth Century Services, Inc. in Kansas City, MO. Twentieth Century had already decided on the need for automating an IE approach, so their task was straight forward: form a research group with the goal of comparing CASE vendOrs and recommending one toolset.
Citation: Eaton, R. & Hayes, K. (1991). CASE Weight Test: A hands on approach to comparing and selecting CASE tools at Twentieth Century Services. CASE Trends: The Magazine for Computer-Aided Software Engineering, 3(8), 18-19
Keywords: Software Development; Computer Aided Software Engineering; Databases; Local Area Network (LAN); CASE Tools